(DE) LEGITIMATION STRATEGIES IN THE YEMENI PROXY WAR: DISCOURSE ANALYSIS OF IRANIAN IRNA MEDIA OUTLET - Alghamdi, Fahad Salem J; Surinderpal Kaur; Ayeshah Syed, (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2025)
Since the onset of the Yemeni conflict, marked by the ousting of President Abdu Rabbuh Mansur Hadi's government following a Houthi militant takeover, Iran has emerged as a significant player. It is perceived as backing and supplying arms to the Houthi regime, while Saudi Arabia supports the ousted Yemeni government. This article aims to scrutinize how Iran's official newspaper outlet, IRNA, constructs the Yemeni proxy war and elucidates the strategies employed to legitimize Iran's involvement. To fulfill this objective, 19 IRNA articles published between April 2018 and March 2019 were collected and subjected to analysis using Van Dijk’s socio-cognitive approach to critical discourse analysis. The analysis comprised three layers: global macro structures, thematic analysis, and ideological schemata analysis. The findings unearth Iran's discourse on the Yemeni conflict, emphasizing its denial of direct involvement, portrayal as a mediator seeking peace, and characterization of the Saudi coalition as aggressors, terrorists, and invaders.